Development of eco-friendly washing machine - Sakidin, H. (EDP Sciences, 2017)
A portable, non-electric washing machine powered by human leg identical to cycling is produced in order to fulfil the need of varsity students to wash their clothes in a cheap, eco-friendly and time saving and also to do physical body exercises. A black plastic bin has been used as the main body. At the bottom lies the rotating disk to provide agitation to the water and also cleaning the clothes. Shaft and gears are also been used in the rotating and moving mechanism that is connected to the pedal. This eco-friendly washing machine with an affordable price will benefit the lower income family and also for the college students. © The authors, published by EDP Sciences, 2017.